Representasi Komunikasi Politik Pada Video Epic Rap Battle Of Presidency 2024 - Prayoga, Billy; Wiryany, Detya; Meltareza, Ridma (AGUNA: Jurnal Ilmu Komunikasi, 2025)
This study aims to analyze the semiotics in the video